Pengaruh Net Profit Margin (NPM), Return On Asset (ROA), dan Debt To Equity Ratio (DER) terhadap Dividend Payout Ratio (DPR) pada PT. Hanjaya Mandala Sampoerna Tbk Periode 2012-2024 - Roza Ekawati; Marwan Setiawan (Lembaga Yasin AlSys, 2026)
Research on dividend policy and the factors influencing it continues to develop in the corporate finance literature. However, discussions that specifically examine the effects of Net Profit Margin (NPM), Return on Assets (ROA), and Debt to Equity Ratio (DER) on Dividend Payout Ratio (DPR) at PT Hanjaya Mandala Sampoerna Tbk during the 2012–2024 period still need to be strengthened. This study aims to analyze the effects of NPM, ROA, and DER on DPR. This study employed a quantitative approach with a causal-associative design. The research data consisted of secondary data obtained from the annual financial reports of PT Hanjaya Mandala Sampoerna Tbk during the 2012–2024 period, selected through the purposive sampling technique. Data were collected through documentation study and were then analyzed using multiple linear regression with the assistance of IBM SPSS. The results show that partially, NPM has a positive and significant effect on DPR, whereas ROA and DER have negative and significant effects on DPR. Simultaneously, NPM, ROA, and DER have a significant effect on DPR, with a coefficient of determination of 0.998. These findings broaden understanding of dividend policy in the context of manufacturing companies and emphasize the importance of profitability and capital structure in determining dividend distribution. The implications of this study include theoretical contributions to the development of corporate finance literature and practical contributions for management in formulating more appropriate dividend policies.